Single-Stage Double-Face Preputial Island Flap versus Two-Stage Byars' Flap Repair for Severe Proximal Hypospadias: A Prospective Randomized Study - El-Raheb, Barsoom M.; Guirguis, Nader N.; Elghandour, Mostafa M.; Radwan, Ahmed B.; ElDebeiky, Mohamed (European Journal of Pediatric Surgery, 2025)
The optimal approach for repairing severe hypospadias remains debated. In our institution, the single-stage double-face preputial island flap (DFPIF) has been employed to reduce the number of procedures and costs. Given the resource-limited context, an evidence-based comparison of repair techniques was warranted to inform cost-effective surgical decision-making.A prospective randomized study was conducted on 36 patients with proximal hypospadias and chordee >30 degrees, treated between 2022 and 2025. Patients were randomly allocated to Group A (DFPIF) or Group B (Byars' flap) using a computer-generated block randomization with allocation concealment. All surgeries were performed by the same team. Patients were followed for 12 months. Groups were compared regarding complications, functional, and cosmetic outcomes. Functional outcomes were assessed using parent-reported urinary stream and erection, with objective chordee assessment under anesthesia. Cosmetic results were evaluated using the Hypospadias Objective Scoring Evaluation (HOSE) score and a 10-point parental satisfaction scale. Outcomes were assessed by a blinded team member who was not involved in the operative procedures. Data were analyzed by a blinded analyst.Thirty-six patients were included, with 18 patients in each group. There was no statistically significant difference in complications, except for partial wound dehiscence, which was higher in group A (p = 0.041). Functional and cosmetic outcomes, as well as parental satisfaction, did not differ significantly.While both techniques achieved acceptable early outcomes, the double-face flap group showed higher rates of partial wound dehiscence. Further studies with larger samples and longer follow-up are required to determine long-term efficacy and safety.
Keywords: hypospadias; severe chordee; double-face; single-stage; Byars' flaps